Impacto da aplicação de um modelo programado de atenção ao diabetes no controle metabólico e de comorbidades de pacientes portadores de Diabetes Mellitus tipo 2 em um centro de referência de média complexidade após um ano de sua implementação - Santos, Nícolas Nascimento (2018)
Objective: The aim was to evaluate the metabolic profile and comorbidities control in patients with diabetes mellitus type 2 (DM2) treated at a medium complexity reference center after 1 year of multidisciplinary follow-up. Materials and methods: A cross-sectional study carried out in a mid-complexity care center from May to December 2017. A total of 229 patients with type 2 diabetes mellitus diagnosis were evaluated. The data studied were blood pressure, LDL, HDL, triglycerides, and control frequencies of glycemic levels, hypertension, dyslipidemia and weight, compared with 251 patients in the same center of medium complexity and with same methodology in 2016. Results: The values of glycated hemoglobin had an average of 7.90% ± 2.07%; in glycemic control in diabetes, 51.5% were well controlled and 48.5% were poorly controlled; 70.8% of hypertensive patients were well controlled; 41.8% had well-controlled dyslipidemia; 19.3% had normal weight. Conclusion: It is important to keep continuous and multidisciplinary care of the diabetic patient with the objective of improving their glycemic measures and metabolic comorbidities in order to reduce the risk or avoid the progression of the complications and morbimortality of DM, considering both the high emotional and financial burden brought by such events.